Ossifying fibroma in a dog - Pinho, Roberto Carlos Mourão; Barbosa, André Cavalcante da Silva; Caldas Júnior, Arnaldo de França; Cimões, Renata; dos Santos, Fernando Leandro (Pubvet, 2018)
Epulis refers to any tumor or similar growth on the gingival tissue and is considered the most frequent of benign oral masses in dogs. Epulis is classified into four types based on histological characteristics: fibromatous, ossifying, acanthomatous and giant cell. The aim of the present study was to present knowledge on benign oral tumors and epulides as well as report a clinical case of ossifying epulis in a male dog (Labrador) aged 25 months. The integrated treatment plan initiated with a diagnostic investigations through hematological, biochemical and serological exams for the study of antibodies for ehrlichiosis, anaplasmosis, dirofilariasis and Lyme disease as well as electrocardiogram and intraoral and thoracic x-rays, followed by the removal of the suspected tumor mass through excisional biopsy. The sample was sent for histopathological analysis for the definitive diagnosis, which confirmed ossifying epulis. In conclusion, surgery was the treatment of choice and only a histopathological analysis can confirm the type of oral neoplasm and prognosis.
Keywords: oncology; gingival tissue; dog; fibroma; ossifying